HUBUNGAN SUBJECTIVE WELL - BEING DENGAN BURNOUT PADA PERAWAT DI RSUD KOTA DEPOK PADA MASA PANDEMI COVID - 19 - Renasti Pratiwi, (2022)
The COVID-19 phenomenon has an impact on the community, including health workers as the frontline in handling patients during the COVID-19 pandemic. The role of nurses during the COVID-19 pandemic can affect satisfaction in their lives. Nurses as the frontline handling COVID-19 cases can cause an increase in workload which has an impact on burnout events. This study aims to determine the relationship between subjective well-being and burnout in nurses at The Depok City Hospital during the COVID-19 Pandemic. This research uses quantitative methods with a cross-sectional study approach. The sampling used was purposive sampling with a total sample of 60 nurses. Data collection used questionnaires and analyzed using the Chi - Square test. The results of statistical tests showed no significant association between age (p = 0.979), sex (p = 0.210), last education (p = 1.000), marital status (p = 0.162), and length of service (p = 0.244) with burnout. The conclusion of this study is that there is no significant relationship between subjective well -being (p = 0.051) and burnout where nurses who have low subjective well - being will be at risk of experiencing severe category burnout. This research is expected to be an input and update for hospital management related to subjective well - being and burnout so that nurses can overcome burnout and improve subjective well - being in the future.